Crack propagation and CT imaging of internal cracks in rocks damaged by pre-compression under explosive loading - Qiangqiang Zheng; Pingfeng Li; Ying Xu; Bing Cheng; Hao Hu; Hao Shi; Shoudong Xie (Ain Shams Engineering Journal)
This study investigates the dynamic crack propagation mechanism in damaged rocks under blasting excavation in complex geological conditions. A novel rock fracture analysis method based on pre-compression-induced random damage is proposed, overcoming the limitations of traditional prefabricated crack models. Innovatively, multi-level cyclic static pre-compression is applied to simulate the random damage distribution in engineering-scale rocks, combined with high-resolution computed tomography (CT) imaging to achieve non-destructive 3D visualization of internal crack morphologies under explosive loading. A theoretical model for predicting blast-induced crack propagation radius in damaged sandstone is established and validated through integrated laboratory blast experiments, CT scanning, and PFC-2D numerical simulations, demonstrating a prediction error margin below 5%. Key findings reveal a significant positive correlation between sandstone damage levels and the expansion range of blast-induced cracks as well as crater dimensions. The pre-existing crack network in damaged rocks effectively guides gas wedging effects, unveiling a “weakening-synergistic fracturing” dual mechanism. These results provide theoretical foundations and technical support for optimizing blasting parameters and mitigating dynamic disasters in tunnel engineering under complex geological settings.